Extraction and Characterization of Bis(nioximato)diiodocobaltate(III)- Mixed Complex by Different Organic Solvents - Ennageh Ali-Shattle, Elbashir; Jafar, A.R.; Handaliba, Assiya (Asian Journal of Chemistry, 2010)
This paper reports the studies on extraction of cobalt ion from aqueous solution using 1,2- cyclohexanedione dioxime (nioxime) by different organic solvents, such as, n-hexane, cyclohexane, isoamyl alcohol, chloroform and ethyl acetate at pH 3, in the presence of different halide ions, F–, Cl–, Br–, I– -I2 solutions and in the presence of appreciable concentrations of other transition metal ions up to 1/1000 ratio of Co/M, where M is Ni, Cu or Fe. Metal nioxime-iodide complexes were extracted into different organic solvents and the absorption at 470 nm was measured for each system by means of spectrophotometry. It was found that the extraction efficiency was enhanced in the presence of I–-I2 solution among the halide ions. The optimum extraction was achieved by ethyl acetate as an organic solvent and with cobalt concentration of 0.07 M. where the optical density was 0.8. To isolate the extracted complex, higher concentration of cobalt salt solution was used. The complex Bis(nioximato)diiodocobaltate(III) was isolated and characterized by CHN elemental analysis, UV-Vis and ESR spectroscopy. From the study of the spectra, the proposed structure was deduced. It is a distorted octahedral (tetragonally distorted) with elongation along the z-axis toward the weak ligands of iodide, K[Co(NH)2I2] ; where NH– is nioximato ligand.